The ‘Illah of Riba on Money in Classical Fiqh Perspective and Its Relevance to Modern Money (A Comparative Study of al-Fawākih ad-Dawānī, Ḥāsyiyah al-‘Adawī, and Ḥāsyiyah al-Bājūrī) - Moh. Mahfud Ali Amari Sya’roni; Advan Navis Zubaidi (LPPM Ma'had Aly Sunan Drajat Lamongan, 2026)
This study aims to analyze the ‘illah (legal cause) of riba on money from the perspective of classical fiqh and examine its relevance to modern financial systems, including paper money, digital currencies, and cryptocurrencies. The main focus is on the differing views of scholars regarding two key concepts: ghalabat ats-tsamaniyyah (dominance of the function as a medium of exchange) and muṭlaq ats-tsamaniyyah (general function as a medium of exchange). This research employs a qualitative library research method, with three classical texts as primary sources: al-Fawākih ad-Dawānī, Ḥāsyiyah al-‘Adawī, and Ḥāsyiyah al-Bājūrī. Analysis was conducted using a descriptive-comparative approach and conceptual synthesis. The results show that the difference in determining the ‘illah of riba stems from two methodological approaches: textual versus functional, with Ḥāsyiyah al-‘Adawī emphasizing the maqāṣid dimension and Ḥāsyiyah al-Bājūrī affirming the role of ‘urf. Based on the synthesis of these three texts, it can be concluded that the muṭlaq ats-tsamaniyyah approach is more relevant to modern financial systems because it accommodates various forms of money, including paper money, digital currencies, and cryptocurrencies such as Bitcoin and other crypto assets, provided they function as widely recognized media of exchange. This study contributes to integrating classical fiqh thought with contemporary economic realities, ensuring that riba rulings remain applicable and aligned with the objectives of Shariah in preserving justice and economic welfare.